2010
DOI: 10.1111/j.1365-294x.2010.04730.x
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus analysis of honeyeaters (Aves: Meliphagidae) highlights spatio-temporal heterogeneity in the influence of biogeographic barriers in the Australian monsoonal zone

Abstract: Multilocus studies in phylogenetics and comparative phylogeography have the power to explore a broader spectrum of evolutionary questions than either discipline has alone. To examine the origins of sympatry in a group of closely related birds of mostly mesic eucalypt woodlands in Australia, we reconstructed the relationships among species of Entomyzon and Melithreptus honeyeaters (Aves: Passeriformes: Meliphagidae) using a mitochondrial marker, ND2, and six non-coding nuclear loci (total 4719 base pairs). By s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 72 publications
11
72
0
Order By: Relevance
“…Early sequencebased phylogeographic studies in babblers [Pomatostomus (58)] reported deep divergence across the CB relative to divergence within the eastern and western regions of the continent. Subsequent multilocus analyses of several avian systems revealed mostly Pleistocene divergences across the CB for congeners (59)(60)(61), as well as within species (62,63). Some studies examining divergence across the region have discovered clines (64) or complex reticulate patterns in the form of introgression; for example, in butcherbirds (Cracticus), populations east of the KTEB are introgressed with mtDNA from populations of arid-adapted species to the south that expanded during the last glacial maximum, whereas populations west of the KTEB are not introgressed (65).…”
Section: Key Processes Of Divergence and Reticulation In Naturementioning
confidence: 99%
“…Early sequencebased phylogeographic studies in babblers [Pomatostomus (58)] reported deep divergence across the CB relative to divergence within the eastern and western regions of the continent. Subsequent multilocus analyses of several avian systems revealed mostly Pleistocene divergences across the CB for congeners (59)(60)(61), as well as within species (62,63). Some studies examining divergence across the region have discovered clines (64) or complex reticulate patterns in the form of introgression; for example, in butcherbirds (Cracticus), populations east of the KTEB are introgressed with mtDNA from populations of arid-adapted species to the south that expanded during the last glacial maximum, whereas populations west of the KTEB are not introgressed (65).…”
Section: Key Processes Of Divergence and Reticulation In Naturementioning
confidence: 99%
“…However, phylogeographic studies of birds have shown contradictory patterns across the Carpentarian barrier: strong differentiation (Lee and Edwards 2008; Toon et al. 2010; Kearns et al. 2011) and the apparent absence of any impact on species differentiation (Kearns et al.…”
Section: Discussionmentioning
confidence: 99%
“…2010), “Bonaparte Gap or Barrier” (Toon et al. 2010), Daly River Drainage Barrier (Potter et al. 2012), and the Victoria River Drainage Barrier (Joseph and Omland 2009).…”
Section: Introductionmentioning
confidence: 99%
“…All nectarivorous Passeriformes belong to the oscine clade, which has no fossil record before the Late Oligocene [9]. Calibrated molecular phylogenies including a comprehensive sampling of Nectariniidae and Meliphagidae do not exist, but analyses of smaller subsets suggest their diversification after the Eocene [22,23]. Fossils of crown group Psittaciformes are unknown before the Early Miocene [24], and molecular divergence estimates indicate that the flower-visiting parrot taxa likewise evolved after the Eocene [25].…”
Section: Discussionmentioning
confidence: 99%